Green resource allocation method for intelligent medical treatment‐oriented service in a 5G mobile network. (8th November 2018) - Wang, Yupeng; Liu, Tianlong; Choi, Chang; Wang, Haoxiang
Summary: Due to the development of mobile transmission techniques, more exciting services can be launched that may change our daily lives in more easy and comfortable ways. The introduction of device‐to‐device (D2D) service in future 5G communication systems can extend the service coverage of intelligent medical treatment from hospitals to anywhere inside the network coverage area, which can save precious time and medical resources. As one of the key techniques in a 5G system, D2D technology has attracted extensive attention from academia and industry due to its system performance improvement, user experience enhancement and service extension. However, the introduction of D2D service will tremendously pollute the system transmission environment due to the induced interference, especially in the downlink direction where the interferer is very strong. This situation brings new challenges for effective and green resource utilization. To solve this problem, a green spectrum resource allocation strategy based on the Hungarian method is proposed in this paper to optimize system spectrum efficiency while considering the fairness among users under the assumption that all resources are fully shared by traditional cellular and newly introduced D2D users. To validate the performance of the proposed algorithm, a system‐level Monte Carlo simulation is also conducted, which shows the favorable performance of the proposed algorithm over the traditional greedy algorithm.